Important Aspect For Bilingual Application To Early Childhood - Suhaeni, Neni (EDUPEDIA Publisher, 2023)
Bilingualism has garnered both positive and negative feedback over the years. The proliferation of early childhood education institutions that provide bilingual programs raises concerns regarding the influence on children, particularly in terms of cognitive and linguistic development. Some who argue against it claim that children would endure speech difficulties, yet various studies have shown conflicting findings. This study use the library research approach to investigate the cognitive development of children who begin bilingualism at a young age Although there are still many pros and cons of bilingual concepts and programs in early childhood, research results show that the positive impact is greater than the negative impact. In terms of cognitive development, it shows that bilingual children have better performance than monolinguals. However, this good result is of course supported by several things such as the readiness of the teacher in preparing the program and choosing the right method so that the expected results can be maximized. Thus, it can make the next generation of the nation brilliant in facing future challenges.